CBSE Class 9CBSE
Share
Notifications

View all notifications

Simplify the Following Expressions: (11 + Sqrt11)(11 - Sqrt11) - CBSE Class 9 - Mathematics

Login
Create free account


      Forgot password?

Question

Simplify the following expressions:

`(11 + sqrt11)(11 - sqrt11)`

Solution

We know that `(a + b)(a - b) = a^2 - b^2` We will use this property to simplify the expression

`(11 + sqrt11)(11 - sqrt11)`

`∴ (11 + sqrt11)(11 - sqrt11) = 11^2 - (sqrt11)^2`

`= 11 xx 11 - sqrt11 xx sqrt11`

`= 121 - sqrt(11 xx 11)`

`= 121 - (11^2)^(1/2)`

= 121 - 11

= 110

Hence the value of expression is 110.

  Is there an error in this question or solution?

APPEARS IN

Video TutorialsVIEW ALL [1]

Solution Simplify the Following Expressions: (11 + Sqrt11)(11 - Sqrt11) Concept: Operations on Real Numbers.
S
View in app×